The IOC manual of sports injuries : an illustrated guide to the management of injuries in physical activity - Bahr, Roald , 1957-; McCrory, Paul (Wiley-Blackwell, 2012)
"This new book, developed in partnership with the Medical Commission of the International Olympic Committee and edited by the world?s leading authorities in sports medicine, is a comprehensive manual for the diagnosis, management, and continued care of patients with sports injuries. Beautifully illustrated with color illustrations and packed with useful at-a-glance information, it is intended as a go-to guide for primary care physicians and other non-specialist clinicians who provide front-line care for the majority of those who participate in sports or personal fitness activities." -- Provided by publisher.